2019
DOI: 10.1128/iai.00377-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Autorepressing Two-Component Signaling System That Modulates Virulence in Streptococcus suis Serotype 2

Abstract: Streptococcus suis is one of the most important pathogens affecting the swine industry and is also an emerging zoonotic agent for humans. Two-component signaling systems (TCSs) play important roles in the adaptation of pathogenic bacteria to host environments. In this study, we identified a novel TCS, named TCS09HKRR, which facilitated Streptococcus suis serotype 2 (SS2) resistance to clearance by the host immune system and contributed to bacterial pathogenicity. Furthermore, RNA-sequencing analyses identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…As S. suis encounters oxidative stress during the process of infection, PTS may play an important role in the RbpA-mediated adaptation of SS2 to the host environment. It is well known that capsular polysaccharide is a key virulence factor in S. suis [ 50 ]. Previous study showed that capsular polysaccharide biosynthesis of S. suis is affected by the availability of glucose or other carbohydrates [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As S. suis encounters oxidative stress during the process of infection, PTS may play an important role in the RbpA-mediated adaptation of SS2 to the host environment. It is well known that capsular polysaccharide is a key virulence factor in S. suis [ 50 ]. Previous study showed that capsular polysaccharide biosynthesis of S. suis is affected by the availability of glucose or other carbohydrates [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from the robA and WT strains and further sent to Novogene (Tianjin, China) to generate the transcriptome library, which was sequenced using the Illumina HiSeq 2000 platform as described previously (Zhong et al, 2018(Zhong et al, , 2019. The transcriptome reads against the reference sequence of strain HZ were mapped by the TopHat2 software, while the differentially expressed genes in the transcriptomic data were identified by the Cuffdiff program.…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…cDNA was synthesized using the HiScriptII first-strand cDNA synthesis kit (Vazyme). The relative amount of target gene mRNA was normalized to the housekeeping gene parC transcript [39]. The relative fold change was calculated by the threshold cycle (2 −ΔΔCT ) method [40].…”
Section: Rna Isolation and Qrt-pcr Analysismentioning
confidence: 99%